STUNTING DAN PROFIL EKONOMI MASYARAKAT DI ACEH - Cut Putri Asnawati; Muhammad Ilhamsyah Siregar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
Abstract This study aims to analyze the likelihood of mothers to have stunted children with using economic and social profile in Aceh. The method used in this study is a quantitative analysis method with a logistical model. The data used is secondary data. The data consisted of cross section data, obtained from SUSENAS March, 2018, and the Provincial Statistics Agency (BPS) of Aceh Province in 2018. The variables used were the family size, breast milk feeding, access to water and sanitation, and visits to health facilities during pregnancy. The results showed that the coefficient value of the variable number of family members was positive, the more the number of children would increase the risk of giving birth to stunting children. While the coefficient of access to clean water, daily protein consumption and visits to health facilities during pregnancy and childbirth are all negative. This shows that safer access to clean water, adequate daily protein consumption and frequent visits to FASKES during pregnancy and childbirth will reduce the risk of giving birth to a stunting child. These variables are statistically significant at the 95 confidence level. Keywords: Stunted, family size, breastfeeding, sanitation, Aceh